2022
DOI: 10.3390/data7110164
|View full text |Cite
|
Sign up to set email alerts
|

CoviRx: A User-Friendly Interface for Systematic Down-Selection of Repurposed Drug Candidates for COVID-19

Abstract: Although various vaccines are now commercially available, they have not been able to stop the spread of COVID-19 infection completely. An excellent strategy to get safe, effective, and affordable COVID-19 treatments quickly is to repurpose drugs that are already approved for other diseases. The process of developing an accurate and standardized drug repurposing dataset requires considerable resources and expertise due to numerous commercially available drugs that could be potentially used to address the SARS-C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The study used an ensemble algorithm to cross-validate antibody response from variable populations to predict pathogenic surveillance. These approaches, as reported previously by the CoviRx database for COVID-19 [ 132 ] in addition to multiomics, has the potential to provide much more rapid and reliable outcomes of nutritional solutions to protozoal MDR infection agents.…”
Section: Application Of Multiomics In High-throughput Analysis Of Gut...mentioning
confidence: 97%
“…The study used an ensemble algorithm to cross-validate antibody response from variable populations to predict pathogenic surveillance. These approaches, as reported previously by the CoviRx database for COVID-19 [ 132 ] in addition to multiomics, has the potential to provide much more rapid and reliable outcomes of nutritional solutions to protozoal MDR infection agents.…”
Section: Application Of Multiomics In High-throughput Analysis Of Gut...mentioning
confidence: 97%
“…Therefore, the quest to identify potential molecules to treat COVID-19 and PASC is still ongoing. We developed a systematic approach to catalogue all FDA/TGA approved drugs available in the Compounds Australia collection [25]; down-select 214 likely candidates [26]; evaluate in vitro/ex vivo efficacy of the top 12 leads [14]; and screen the 214 candidates using molecular modeling techniques to identify additional leads [27]. In our latter list is present a bisphosphonate molecule called alendronate, and we came across a parallel study which observed that humans who used alendronate (and another bisphosphonate called zoledronate) had lower odds ratios (typically 0.21-0.29) of testing for SARS-CoV-2 infection, COVID-19 diagnosis and COVID-19-related hospitalization [28].…”
Section: Objectives Of This Workmentioning
confidence: 99%
“…We have recently employed an in silico approach to down-select nine approved drugs (plus three anti-SARS-CoV-2 control drugs) for assessment using a commercially-sourced ALI model of the human airway epithelium [11][12][13]. Five drugs that showed promise were further evaluated against both Delta and Omicron variants of concern (VOC), with fluvoxamine exhibiting anti-SARS-CoV-2 activity, albeit at concentrations higher than can be achieved in patients [13].…”
Section: Introductionmentioning
confidence: 99%